Improvement on engineering properties of Pekan soft clay treated with hydrated lime as a method of soil stabilizer - Nurul Zawarni , Zaim (2012)
Clay can be categorized as a troubled land. Low soil strength and height of the pressure forces applied to be among the main factors why care must be taken into account when making plans to build something on that site. Because of this problem, a study of land on the basic characteristics of soil and soil stress to be done. This project contributes to the engineering analysis features that meet the requirements of the National Lime Association as the limits of plasticity index and the percentage of land after land sieve analysis. Many attempts have been made to study examples of suitable land as a sample. Overall, the test results against plastic index and sieving the soil are likely to correspond to the increase in soil strength. From the requirements required by the National Lime Association, land in Pekan, Pahang fit to undergo the process of improving the strength of the soil. Pekan clay more than 90% passing 0.075mm sieve and plasticity reaches more than 10%. Based on soil plasticity chart, Pekan clay identified as clay with medium plasticity level. Based on Eades-Grim test, the percentage of lime obtained from the experiments is 4 percent and a maximum pH obtained was pH 11.8. This test shows the results of obtained pH value give almost the same value from 4 percent to 12 percent mixture of lime. Tests on the stress of clay soils after treatment with lime showed clay in Pekan, Pahang is 116 kPa.